[PP.15.22] EPINEPHRINE IS REQUIRED FOR PREVENTING BLOOD PRESSURE OVERSHOOT AND THUS CARDIAC HYPERTROPHY IN CHRONIC EXERCISE. (September 2017) - Martinho, R.; Mendes, P.; Leite, S.; Maia-Moço, L.; Leite-Moreira, A.; Lourenço, A.; Moreira-Rodrigues, M.
Abstract : Objective: Phenylethanolamine-N-methyltransferase-knockout (Pnmt-KO) mice are epinephrine-deficient and appear to have concentric heart remodelling. Although Pnmt-KO mice resting blood pressure is normal, it becomes higher than wild type mice during acute treadmill exercise. However, the role of epinephrine in cardiovascular response to chronic exercise remains unclear. Therefore, the aim of this study was to evaluate heart morphological, functional and molecular alterations after chronic exercise in epinephrine-deficient mice. Design and method: PCR-based genotyping was performed at the Pnmt locus of Pnmt-KO (Pnmt-/-) and wild-type (WT) mice (Pnmt+/+) (129x1/SvJ). Epinephrine and norepinephrine were quantified by RP-HPLC-ED, in adrenal glands. Animals were submitted to a 6-week chronic exercise training program performed on a motor treadmill until 20 m/min, for 55 minutes, 5 days per week. Blood pressure was determined by a photoelectric pulse detector after treadmill exercise, at rest. Mice were anaesthetized and cardiac morphology and function were evaluated by echocardiography and hemodynamics. Molecular markers of cardiac hypertrophy were evaluated by real-time PCR. Results: Systolic blood pressure was significantly increased in Pnmt-KO when compared to WT mice. A significant increase was found in left ventricular posterior wall thickness and mass in trained Pnmt-KO compared to trained WT mice, without significant differences in LV volume. Compared to basal parameters, acute β1-adrenergic stimulation with dobutamine increased cardiac index in trained WT mice, contrary to trained Pnmt-KO mice. In the left ventricle, mRNA expression of ANP and IGF-1 were significantly increased in trained Pnmt-KO mice when compared to trained WT mice. Conclusions: In conclusion, increased blood pressure overshoot in response to exercise appears to be associated with an increase in left ventricular posterior wall thickness and mass in chronic exercise, suggesting a concentric hypertrophy of the left ventricle in trained Pnmt-KO mice. In addition, acute hemodynamic stress induced by dobutamine increased systolic function index in trained WT, contrary to trained Pnmt-KO mice, suggesting a possible initial stage of pathological cardiac hypertrophy in these mice. Therefore, epinephrine appears to be essential for prevention of blood pressure overshoot and thus cardiac hypertrophy in chronic exercise.